Lecturer’s Personal and Social Competence Toward Students’ Writing Proficiency in EFL Classroom - Limbong, Sunarlia; Alberto; Frans Tandibura (Journal of English Education and Teaching, 2023)
The competency of a lecturer is required for a successful learning process that leads to increased student accomplishment. The present study investigates (1) the profile of students' writing skills at the Port Shipping Management Department of Polytechnic of Makassar Merchant Marine (PIP) through a writing test, and (2) the influence of lecturers' personal and social competence on students' writing proficiency in English as a Foreign Language (EFL) classroom settings using qualitative data. The study employed purposive sampling to select 3 lecturers and 30 second-semester students from the Port Shipping Management Department of PIP. Quantitative data were collected through a writing test administered to the 30 students, while qualitative data were gathered using semi-structured interviews with the 5 lecturers, focus group discussions with the students, and classroom observations. The findings revealed various levels of writing proficiency among PIP students and highlighted the positive impact of lecturers' personal and social competence on students' writing proficiency. The better the personal influence and social competence of the lecturers, the better the students' writing capabilities are. The study emphasizes the need for continued development of lecturers' personal and social competence to foster a supportive and engaging learning environment in maritime education and training.